Orientasi Pembelajaran, Orientasi Pasar Dan Keunggulan Bersaing Di PTN Provinsi Sulawesi Utara - Manaroinsong, Marini (JURNAL RISET BISNIS DAN MANAJEMEN, 2013)
The results of research are as follows: (1) learning orientation has significant and positive influence on competitive advantage of state university. This influence shows that the higher learning orientation applied by the management of state university, the higher competitive advantage is. It means that learning orientation is a strong determinant factor of competitive advantage for state university; (2) market orientation has significant and positive influence on competitive advantage. It shows that the higher market orientation, the higher competitive advantage of state university is. Therefore, competitive advantage of state university besides determined by other factors, cannot neglect market orientation for it has strong determination; and (3) both learning orientation and market orientation simultaneously have significant and positive influence on competitive advantage. It shows that the higher learning orientation and market orientation, the higher competitive advantage of state university is